2014
DOI: 10.1007/s12033-014-9795-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Cardiac Markers in Differentiated Cells from Menstrual Blood and Bone Marrow-Derived Stem Cells In Vitro

Abstract: In recent years, menstrual blood-derived stem cells (MenSCs) have been introduced as easily accessible and refreshing stem cell source without ethical considerations in the field of regenerative medicine. The aim of this study was to investigate in vitro cardiac differentiation capacity of MenSCs compared to bone marrow-derived stem cells (BMSCs) under two protocols using 5-aza-2'-deoxycytidine (5-aza) and basic fibroblast growth factor (bFGF). Our data revealed that differentiated MenSCs and BMSCs acquired so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…This suggests that FGF2 has a key role in differentiating cardiac cells from MSC sources. MenSC had greater capacity than bmMSC to differentiate toward cardiomyocytes regardless of the differentiation protocol (Rahimi et al, 2014).…”
Section: Mesodermal Lineage Differentiationmentioning
confidence: 91%
“…This suggests that FGF2 has a key role in differentiating cardiac cells from MSC sources. MenSC had greater capacity than bmMSC to differentiate toward cardiomyocytes regardless of the differentiation protocol (Rahimi et al, 2014).…”
Section: Mesodermal Lineage Differentiationmentioning
confidence: 91%
“…Differentiation capacity of these cells toward different lineage such as osteoblast, adipoblast, oligodendrocyte progenitor cell and neuron have been investigated in some studies [33,34]. Rahimi et al used menstrual blood stem cells to be differentiated to cardiomyocytes and found higher differentiation potential of this cells toward cardiomyocytes compared with BMSCs [35].…”
Section: Discussionmentioning
confidence: 99%
“…MenSCs express OCT-4, whereas BMSCs do not [ 36 38 , 41 ]. Unlike with other MSCs, expression of MSCs markers, CD29, CD44, and CD90 in MenSCs reduced to less than 95% when the cultured cells reached P10, indicating a declined stemness activity of MenSCs upon more passaging.…”
Section: Comparison Of Menscs With Mscs From Other Sourcesmentioning
confidence: 99%
“…Interestingly, this inferiority in osteogenic differentiation can be successfully overcome by substitution of human platelet lysate with FBS. MenSCs were more able to be specialized into cardiomyocytes than BMSCs [ 41 ]. Although the ability of MenSCs to differentiate into neural cells was inferior to BMSCs, the levels of functional calcium, potassium, and sodium channel genes in MenSCs during the process of differentiation were significantly higher than those in BMSCs [ 42 ].…”
Section: Comparison Of Menscs With Mscs From Other Sourcesmentioning
confidence: 99%